Weekly iron supplementation reduces anemia prevalence by 1/3 in preschool children Suplementação semanal com sulfato ferroso reduz em 1/3 a prevalência de anemia em pré-escolares - Gisela Soares Brunken; Pascoal Torres Muniz; Solanyara Maria da Silva (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2004)
A weekly medication scheme, followed by nutritional guidance on diets in child-care centers, was evaluated in order to make it feasible for routine use. The study was conducted in six child-care centers in the town of Cuiabá - Brazil. The supplement (6 mg/kg) was provided on a weekly basis to all children (n=178) less than three years old during four months at the institution by the classroom staff. After this initial phase, nutritional guidance was provided regarding the child-care center's normal diet as a way to control hemoglobin levels. This is an intervention study whose individuals were examined at three different periods: at the beginning of treatment (T0); after four months of iron supplementation (T1) and after five months of nutritional guidance (T2). Hemoglobin measurements were obtained using a portable hemoglobinometer - HemoCue. A significant improvement was observed in the hemoglobin levels of anemic children after controlling for age and initial hemoglobin. The hemoglobin concentration of these children improved an average of 0.1 g/l after each dose of iron sulfate. At the end of four months there was an average gain of 1.6 g/l, and prevalence of anemia reduced by 1/3, sufficient to meet the United Nations target adopted by Brazil. At the end of nine months (four months of weekly drug intervention followed by 5 months of nutritional guidance) the prevalence of anemia dropped by 1/4 in the child-care centers. The intervention proved to be feasible for child-care centers and pre-school population. Um esquema terapêutico semanal, seguido de orientação alimentar aos cardápios, foi avaliado com o intuito de verificar viabilidade como rotina em creches. O estudo foi realizado em seis creches no município de Cuiabá. O suplemento (6 mg/kg) foi oferecido semanalmente a todas as crianças (n=178) menores de 3 anos durante 4 meses, na própria Instituição, pelas funcionárias. Após essa primeira etapa seguiram-se orientações alimentares ao cardápio da creche, como forma de controle desses níveis de hemoglobina. Este é um estudo de intervenção, onde os indivíduos foram avaliados em três momentos: no início do tratamento (T0), após a primeira etapa (T1) e após a segunda etapa (T2). Para avaliação da hemoglobina foi utilizado hemoglobinômetro portátil - HemoCue. Houve um acréscimo significativo na hemoglobina, após controle para idade e hemoglobina inicial. A concentração de hemoglobina aumentou em média 0,1 g/l após cada dose de sulfato ferroso. Ao final de quatro meses de suplementação houve um acréscimo médio de 1,6 g/l, e a prevalência de anemia reduziu para 1/3, suficiente para atingir a meta das Nações Unidas adotada pelo Brasil. Ao final de nove meses (quatro meses de suplementação medicamentosa semanal, seguida de cinco meses de orientação alimentar), a prevalência de anemia reduziu para 1/4. A intervenção mostrou-se viável para utilização em diferentes creches e em pré-escolares.